2015
DOI: 10.4040/jkan.2015.45.3.449
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Breastfeeding Knowledge, Attitude and Interest with Breastfeeding Duration: A Cross-sectional Web-based Study

Abstract: Purpose: Maternal knowledge, positive attitudes and interest toward breastfeeding may improve the sustainability of breastfeeding. This study examined the associations of knowledge, attitudes, and interest toward breastfeeding with the duration of breastfeeding in Korean mothers who used the internet. Methods: We conducted a cross-sectional study of 604 Korean mothers who breastfed their babies. Mothers were recruited through the internet and their knowledge, attitudes and interest toward breastfeeding were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…This finding consistent with studies done in United States (Persad & Mensinger, 2008), United Kingdom (Shaker, Scott, & Reid, 2004), Ireland (Sittlington, Stewart-Knox, Wright, Bradbury, & Scott, 2007), Canada (Twells et al, 2014) and Korea (Kang, Choi, Hyun, & Lee, 2015) who found that breastfeeding intention is associated with positive breastfeeding attitudes.…”
Section: Discussionsupporting
confidence: 82%
“…This finding consistent with studies done in United States (Persad & Mensinger, 2008), United Kingdom (Shaker, Scott, & Reid, 2004), Ireland (Sittlington, Stewart-Knox, Wright, Bradbury, & Scott, 2007), Canada (Twells et al, 2014) and Korea (Kang, Choi, Hyun, & Lee, 2015) who found that breastfeeding intention is associated with positive breastfeeding attitudes.…”
Section: Discussionsupporting
confidence: 82%
“…Recent studies have shown that maternal knowledge and interest were associated with a longer duration of BF and intention to breastfeed in Korea. 8 Moreover, recent studies have found that maternal knowledge about infant health benefits was directly related to their intention to exclusively breastfeed in diverse urban populations. 9 Another study has shown the significant roles hospitals play in BF initiation and promotion, with rooming-in care of infants, initial BF practices, and education during hospital stay as important practices.…”
Section: Introductionmentioning
confidence: 99%
“…The recommendation of the World Health Organization (WHO) is exclusive breastfeeding (EBF) of infants during the first six months of life, and breastfeeding (BF) for two years or beyond with complementary foods for achieving optimal growth and health ( 1 ) . In addition to providing essential nutrients to infants, breastmilk has been shown to be related to decreased sudden infant death syndrome, respiratory-gastrointestinal tract infections, and allergic diseases, as well as a lower risk of developing obesity, cardiovascular disease, diabetes, and hematologic malignancies in future life ( 2 , 3 , 4 ) . Reduction in postpartum blood loss due to increased uterine activity and greater weight loss compared with mothers who bottle feed are the reported benefits of BF for mothers ( 2 , 3 ) .…”
Section: Introductionmentioning
confidence: 99%